Analysis of PAI Learning Outcome Problems for SDN Dongkal 1 Students in Era 4.0 - Amalia Khoiriyah; Lilis Karyawati; Nia Karnia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The article is defined to be focused in the development of PAI indonesia’s curriculum in relation to 21st century competency requirements. This study is fovused within a observation research in which authors observe, interview, and analyze a variety of information from a variety of relevant sources. The beginning of the 21st century noted with the rapid development of information and communication technology and the beginning of free competition between other nations in curriculum aspects. As a result, student life today is much differ than and much complicated than it used to be. Children tend to be lazy and have lower IQs without any desire to learn. It seems can be a problem that can lead to destruction for indonesia’s educational value. Within the power of connection and technology, the writer can take apart with a destination to increase a value of PAI curriculum and look for deficiances in education in education in order to inform people in the education sector, to find a way out of a problem with a new inovation. This study uses a observation survey method to collect and analyze field data data. The data of research results take a part of adjustment of the Islamic education curriculum in the 4.0 era. The traditional blending and technology defense method is blended learning, and the content of things must adapt to the state and needs of skills in the 4.0 era, comprehensive assessment and shared responsibility (educational ecosystem). Educators had to direct their students value without being disturbed with 4.0 era.